Teacher’s Intention to Report Child Abuse and Neglect in Romania: A Mixed-method Study - CRISTESCU, Delia (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2024)
Child abuse and neglect (CAN) have long-lasting effects on a child’s physical, social, and psychological development. Teachers have a unique position to identify, protect, and intervene in these cases, but they often fail to help children in need. This study aims to describe and investigate the factors associated with CAN reporting behavior of school teachers and counselors from Romania using the Theory of Planned Behavior (TPB) as a framework. Methods. We conducted a mixed-method study using a modified version of the Child Abuse Intention to Report Scale (CARIS-R). 1025 teachers (91,7% female) participated in the survey. Quantitative and qualitative data analyses were performed to explore the predictors of intention to report CAN and the reasons to report CAN. Results. More than half of the teachers (51.9%) suspected at least one CAN case, but only 28.1% reported their concerns. Attitudes towards child discipline and professional responsibility, direct subjective norms, and perceived behavioral control were significant predictors of intention to report CAN. Eight categories of reasons might influence a teacher’s decision to report CAN, including the type of abuse, the teacher’s characteristics, or the perceived social support. Conclusions. This study’s findings contribute to our understanding of the individual factors that can influence teachers’ intention to report CAN in Romania. Teachers from Romania should have the opportunity to participate in evidence-based training, which fosters their confidence in making CAN reports.